Online Virtual Classroom Management using WebRTC Based Flipped Model - Raswa Raswa; Shumarudin Shumarudin; Eka Ismantohadi; Jamaluddin Jamaluddin (Pendidikan Administrasi Perkantoran, Universitas Negeri Makassar, 2021)
Online learning has had a tremendous impact on the field of education but has the effect of lowering the quality of academic integrity compared to face-to-face learning. The purpose of this study is to produce an online learning system that uses the flipped model in an online virtual classroom with the application of WebRTC technology, so that the constraints on the quality of academic integrity in these learning activities can be overcome. The research method used was an experiment with a One-Group Pretest-Posttest Design. The sampling technique used is cluster sampling. The results showed that the use of the flipped learning model in an online virtual classroom based on WebRTC was categorized as better in improving the quality of students' academic integrity when compared to the use of the Flipped learning model without WebRTC. This research can be used as a reference in managing online learning systems using the Flipped model based on WebRTC because previous research focused on the Flipped learning model in WebRTC-based online virtual classrooms that can improve the quality of student learning integrity.